The intricate path of forage technologies in Colombia: An institutional analysis - Enciso, Karen; Triana Ángel, Natalia; Díaz, Manuel Francisco; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2021)
To increase the productivity of tropical cattle systems and at the same time mitigate the environmental impacts of the cattle sector, a strategy of improving the quality and availability of cattle feed has been implemented through substantial improvements in forage germplasm (Herrero et al., 2013; Gerber et al., 2013; Peters et al., 2012). With this objective, significant resources have been allocated for research and development (R&D), which has led to the release of cultivars such as Brachiaria brizantha cv. Toledo (CIAT 26110), B. humidicola cv. Humidicola (CIAT 679) and cv. Llanero (CIAT 6133), and B. ruziziensis cv. Kennedy, as well as Brachiaria hybrids (cvs. Mulato, Mulato II, Caimán, and Cobra) (Peters et al., 2011; Pizarro et al., 2013; Miles et al., 1996). According to research results from several countries, these cultivars show better characteristics in terms of adaptation to different soil and climatic conditions, offer multiple environmental benefits, and provide higher forage quality and quantity (e.g., Peters et al., 2012; Rao et al., 2015).